A perspective from Islamic moral economy: Maqāṣid al-Sharī‘ah vs sustainable development goals - Mohd. Zain, Nor Razinah; Zakariyah, Habeebullah; Mohd Noor, Azman (2020)
Background: The formal emergence of Islamic moral economy in Muslim countries can be traced back after the end of Second World War in 1945. Continuous efforts to have Sharī‘ah compliance economy were made informally by Islamic revivalists even though they were placed under the pressure of colonialism and within a limited space of freedom. Reaching towards 1960’s, the successful experiment of Islamic banking and finance generates a new opportunity to have a comprehensive nature of Islamic moral economy. Islamic banking and finance industry opens a wide legal and economic landscape to practice Islamic moral economy which consistent with the concept of Maqāṣid al-Sharī‘ah. Recently, the United Nations introduced 17 goals of Sustainable Development Goals (SDGs). The SDGs seem to be a set of uniformed goals in reaching a balanced development among countries; while coping with the side effects of maximization of profit and capitalism.